Healthcare utilisation and costs of home mechanical ventilation. Issue 7 (26th January 2018) - Nonoyama, Mika L; McKim, Douglas A; Road, Jeremy; Guerriere, Denise; Coyte, Peter C; Wasilewski, Marina; Avendano, Monica; Katz, Sherri L; Amin, Reshma; Goldstein, Roger; Zagorski, Brandon; Rose, Louise
Abstract : Background: Individuals using home mechanical ventilation (HMV) frequently choose to live at home for quality of life, despite financial burden. Previous studies of healthcare utilisation and costs do not consider public and private expenditures, including caregiver time. Objectives: To determine public and private healthcare utilisation and costs for HMV users living at home in two Canadian provinces, and examine factors associated with higher costs. Methods: Longitudinal, prospective observational cost analysis study (April 2012 to August 2015) collecting data on public and private (out-of-pocket, third-party insurance, caregiving) costs every 2 weeks for 6 months using the Ambulatory and Home Care Record. Functional Independence Measure (FIM) was used at baseline and study completion. Regression models examined variables associated with total monthly costs selected a priori using Andersen and Newman's framework for healthcare utilisation, relevant literature, and clinical expertise. Data are reported in 2015 Canadian dollars ($C1=US$0.78=₤0.51=€0.71). Results: We enrolled 134 HMV users; 95 with family caregivers. Overall median (IQR) monthly healthcare cost was $5275 ($2291–$10 181) with $2410 (58%) publicly funded; $1609 (39%) family caregiving; and $141 (3%) out-of-pocket (<1% third-party insurance). Median healthcare costs were $8733 ($5868–$15 274) for those invasively ventilated and $3925 ($1212–$7390) for non-invasive ventilation. Variables associated with highest monthly costs were amyotrophic lateral sclerosis (1.88, 95% CI 1.09 to 3.26, P<0.03) and lower FIM quintiles (higher dependency) (up to 6.98, 95% CI 3.88 to 12.55, P<0.0001) adjusting for age, sex, tracheostomy and ventilation duration. Conclusions: For HMV users, most healthcare costs were publicly supported or associated with family caregiving. Highest costs were incurred by the most dependent users. Understanding healthcare costs for HMV users will inform policy decisions to optimise resource allocation, helping individuals live at home while minimising caregiver burden.